2020
DOI: 10.1002/jeq2.20158
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of wheat production and wheat‐based crop rotations

Abstract: In the northern Great Plains (NGP), wheat is the primary grain commodity. There is a need for the NGP to have a detailed analysis of environmental impacts for wheatbased agricultural production systems to better understand regional agroecosystems. This article provides a cradle-to-field gate life cycle assessment (LCA) for NGP dryland wheat (Triticum aestivum L.) production. The environmental impacts for winter wheat production using crop rotation and agricultural intensification are quantified. Fourteen no-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This provides ample opportunities to advance (n)LCA by considering nutritional provision from rotational agricultural systems, an understudied aspect in terms of agri‐food sustainability and food security, which produce multiple food products (e.g. Shrestha et al, 2020 ). For example, nutritional metrics can be applied to the four systems trialed at Palo a Pique (each of which provides different agricultural products) to determine which system produces the most nutritionally‐ and environmentally friendly outputs at a land‐use level rather than at an individual product level, e.g.…”
Section: Future Directions For (N) Lca To Improve ...mentioning
confidence: 99%
“…This provides ample opportunities to advance (n)LCA by considering nutritional provision from rotational agricultural systems, an understudied aspect in terms of agri‐food sustainability and food security, which produce multiple food products (e.g. Shrestha et al, 2020 ). For example, nutritional metrics can be applied to the four systems trialed at Palo a Pique (each of which provides different agricultural products) to determine which system produces the most nutritionally‐ and environmentally friendly outputs at a land‐use level rather than at an individual product level, e.g.…”
Section: Future Directions For (N) Lca To Improve ...mentioning
confidence: 99%
“…Taking the hectare of land as FU, they concluded that rotations are affected by the mineral fertilization processes that would be avoided in addition to the production of electricity for water pumping. Among the studies analyzed there is only one related to the U.S. area, in particular the research of Shresta et al (2020) [35] who evaluated the life cycle (from cradle to gate) of wheat in the arid areas of the "Northern Great Plains" (USA-Canada), taking as reference 5 impact categories and as FU 1 kg of winter wheat, rotating the crops. Based on the analysis, none of the rotations obtained better results in terms of environmental impact, while changing calculation methodology (endpoints), when wheat is alternated with oilseeds and legumes, lower damages are obtained.…”
Section: Major Cerealsmentioning
confidence: 99%
“…In fact, when a comparison was made between national wheat production and the respective Global Warming Potentials (GWPs), it emerged that it was possible to proceed with this analysis only in the few cases in which an equal FU was available. Another limitation of the study is the low scientific production, so it was possible to proceed with the analysis only in China and America, whose GWP is respectively 1,210 kg CO2 eq × 1 ton [30] and 270 kg CO2 × 1 ton [35]. Therefore, multiplying these values by Chinese and U.S. wheat production, comparing the two productions, it emerged that the Chinese one, the largest at global level, is also more impactful than the American one (Figure 2), which produces only 9% of the total CO2 emissions of the Chinese one with a production equal to 40% of the first producer.…”
Section: Major Cerealsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of agrochemicals to enhance crop yield endangers biodiversity and ecosystems (Malaj et al, 2020). Reduced fertilizer usage by replacing it with biofertilizers (Klaic et al, 2021;Tsachidou et al, 2021), ensuring a sustained release of nutrients using amendments such as biochar (Ullah et al, 2020) and nanoparticles (Avellan et al, 2021), soil organic carbon sequestration (Abera et al, 2021;Brombin et al, 2020;Mancinelli et al, 2020), crop rotation (Hirzel et al, 2021;Shrestha et al, 2020), intercropping (Shah et al, 2021), adoption of agroecological practices (Abbasi Surki et al, 2021;Rakotovao et al, 2021), utilization of crop residues for maintaining soil fertility (Berazneva et al, 2018; are important for ensuring socio-ecological sustainability.…”
Section: Research Themesmentioning
confidence: 99%